Boundary problems for the wave equation with the Lévy Laplacian in Shilov’s class - Feller, M. N.; Belopolskaya, Ya. I.; Albeverio, S. (Methods of Functional Analysis and Topology, 2010)
We present solutions to some boundary value and initial-boundary value problems for the "wave" equation with the infinite dimensional L\’evy Laplacian Δ _L ^2 U(t,x)t^2=Δ_LU(t,x) in the Shilov class of functions.